Observation of snake (Colubridae) predation by yellow-tailed woolly monkeys (Lagothrix flavicauda) at El Toro study site, Peru - Fack, Vinciane; Shanee, Sam; Drubbel, Régine Vercauteren; Santoscoy, Marcela Del Viento; Meunier, Hélène; Vercauteren, Martine (Neotropical Primates, 2018)
No abstract